Combined use of Azolla and loach suppressed paddy weeds and increased organic rice yield: second season results - Weiguo Cheng; Miwa Takei; Chizuru Sato; Valensi Kautsar; Yuka Sasaki; Satoru Sato; Keitaro Tawaraya; Hironori Yasuda (Journal of Wetlands Environmental Management, 2015)
Organic farming uses alternatives to agricultural chemicals such as synthetic fertilizers and pesticides. The primary challenge in organic rice farming is controlling weeds without using herbicides and improving rice yield without chemical fertilizers. In our previous paper entitled as combined use of Azolla and loach suppressed weed Monochoria vaginalis and increased rice yield without agrochemicals, we reported the first year rice growth season results from an in situ container experiment. The experiment was designed with 4 treatments—control (with neither Azolla nor loach), Azolla (Azolla alone), loach (loach alone), and Az+Lo (combined Azolla and loach)—with 3 replications each. The first year results showed that combined use of Azolla and loach was successful in weed suppression and increase in rice yield in 2012. In this paper, we report the second year results from the continuous container experiment in 2013. M.vaginalis emergences were very low in second year rice growth season on all treatments. Compared first year, the rice yields decreased in second year on all treatments due to different weather condition and with or without organic soybean oil cake application between two rice growth seasons. The second year results also showed the raising loach had a stronger effect to increase tiller and panicle numbers, and spikelet number per panicle, then improve rice yields to 2.3 times than control. The Azolla residues left from first year have weaker effect on rice growth and yield, but increase soil organic matter accumulation at second year. The two years study indicated that combined use of Azolla and loach can meet two of the greatest challenges in organic rice production: providing effective weed control and improving rice nutrition without agrochemicals.